The Origin, Applications, and Breeding Goals of Jujube in China - Menghan Wu; Yaoxi Liu; Tingjian Jiang; Yiteng Liu; Zhuo Chen; Xiaofei Wang; Huafeng Yue; Fangdong Li; Gaopu Zhu; Mengmeng Zhang (Horticulturae)
Jujube (Ziziphus jujuba Mill.) is one of the three traditional woody crop species in China, where it originated from the middle and lower reaches of the Yellow River. Jujube is considered one of the oldest cultivated fruit trees species in the world, as its utilization can be traced back to more than 7000 years ago. The jujube has important nutritional, economic, and ecological values, hence it is well received by both planters and consumers. At present, jujube cultivation has spread to more than 48 countries and provides a pathway for Chinese farmers to produce a lucrative cash crop. Jujube is regarded as a superfruit of the future due to its excellent nutritional profile. Social progress and economic shifts leading to the improvement of living standards influence the value of jujube to consumers, who have gradually shifted toward functional foods, while at the same time, consumer desires and environmental pressures change the breeding goals for new jujube varieties. In this review, we summarize the origin, classification, and historical, as well as modern, uses of jujube. We also provide some advice on the establishment of breeding objectives in this new period of jujube development. This review aims to provide useful references for researchers new to jujube, to guide shareholders in the jujube industry, and to formulate breeding objectives for the modern development of elite jujube cultivars.